"Context" in healthcare information technology resistance: A systematic review of extant literature and agenda for future research. (April 2020) - Kumar, Mayank; Singh, Jang Bahadur; Chandwani, Rajesh; Gupta, Agam
Abstract: Resistance to Healthcare Information Technologies (HIT) continues to be a major challenge that hampers the realization of benefits. Attending to the noted significance of "context" in IT resistance, we carried out this review to understand how the "context" of healthcare in the extant HIT resistance literature has been studied. Based on a review of HIT resistance across 19 IS journals and 5 major IS conferences we organize and summarize the literature around the interaction of people, practice, and technology and provide several significant possibilities for future research.